Single Slit to Curve-Single Slit, Double Slit to Curve-Double Slit to Non-Parallel-Double Slit to Non-Parallel-Curve-Double Slit Experiments -PhotoWave Phenomena (London Journal of Research In Science: Natural and Formal, 2024)
Feynman (1956) called the double slit experiment " contains the only mystery. We cannot make the mystery go away by explaining how it works". The photons are described by probability wave functions. The wave functions collapse to photons when landed on detector. However, the collapse of the wave function leads to the inconsistent/incomplete of the quantum mechanics (Penrose, 2022). In this article, we confirm that the diaphragm does not change the nature of the light passing through it. Then we perform multi experiments to show that, before and after passing through the diaphragm, the light is photons, not waves. It is photons that produce the interference pattern, we refer to it as PhotoWave Phenomena. We show for the first time the novel phenomena, new mysteries: (1) a same single produces the non-diffraction pattern near the diaphragm, which gradually evolves to the orthogonal diffraction patterns; (2) a curve-single slit produces the non-diffraction pattern near the diaphragm, which gradually evolves to Hourglass-shape patterns; (3) a double slit produces the non-interference patterns near the diaphragm, which gradually evolves to the orthogonal interference patterns; (4) a non-parallel-double-slits produces the non-wave patterns near the diaphragm, which gradually evolves to the hybrid patterns; (5) a curved-double slit produces Arc-interference pattern near the diaphragm and Point-symmetry interference patterns near/on the detector; (6) Non-parallel-curve-double slit produces Butterfly-shape interference patterns; (7) simple differences in the shapes of slits lead to the profound differences in the pattern evolutions and in the final patterns, we referred to which as Optical-Butterfly phenomena. We referred to above novel phenomena as PhotoWave phenomena. The PhotoWave phenomena support Penroses statement. To explain completely/consistently PhotoWave phenomena is a challenge. PhotoWave experiments provide the comprehensive phenomena for further developing theoretical model to study the nature of the light, the complementarity principle, and the light wave theories.
Keywords: origin of life; energy dissipation; entropy production; constrained dynamic optimization; efficient decentralized decision making; stochastic dependence; stochastic processes; alternative for time series financial models; parameter dependence method of construction; k-Markovianity.; double slit; pattern evolution; Particle pattern; Transition pattern; Non-interference pattern; non-parallel double slit; hybrid pattern; curved-double slit; Arc interference pattern; Point-symmetry interference pattern; nonparallel-curve-double slit; Butterfly-shape pattern; Optical Butterfly phenomena